Pro Zeca de Victor Assis Brasil: aspectos do hibridismo na música instrumental brasileira - Leonardo Barreto Linhares (2007)
Study about the recognition of musical elements typical of bebop and baião in Pro Zeca by Brazilian composer and saxophonist Victor Assis Brasil (1945-1981) in its leadsheets (manuscripts and transcription) and the interpretation included in the recording Victor Assis Brasil (1974). The transcription of the theme and improvisation of this historical recording (instrumentation, bass line and harmonic, melodic and rhythmic elements) was the departing point for a descriptive and comparative analysis, which also resorted to historical and theoretical references of performance practices in jazz (GRIDLEY, 2006; LAWN, 1995; HOBSBAWM, 1990, BAKER, 1987) and Brazilian music (GIFFONI, 1997; SIQUEIRA, 1981; SÉVE, 1999). The findings related to both the composition and its interpretation by Victor Assis Brasil point to a hybridization between jazz and baião, in which the characteristics of these genres sometimes remain recognizable and sometimes result in a unique synthesis. The Appendixes include five leadsheets of Pro Zeca: the composer´s manuscript, an anonymous manuscript and the transcriptions of the introduction, the theme and the improvised solo in the composer´s recording.